2022
DOI: 10.1039/d2cy00824f
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline sulfur and oxygen co-doped g-C3N4 nanosheets as an advanced photocatalyst for efficient hydrogen generation

Abstract: Heteroatom doping has become a promising strategy to tailor the band structure and physicochemical properties of graphitic carbon nitride (g-C3N4). However, doping heteroatoms usually lead to decreased crystallinity, thereby an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…5,6 Compared with industrial hydrogen production and electrochemical hydrogen production, photocatalytic hydrogen evolution is undoubtedly the most sustainable and involves least energy consumption. 7 At present, among various semiconductors (such as CdS, [8][9][10] g-C 3 N 4 , [11][12][13] and TiO 2 (ref. 14 and 15)) as photocatalysts, titanium dioxide (TiO 2 ) is considered to be the most suitable photocatalyst for hydrogen production via water splitting due to its low cost, nontoxicity, high catalytic selectivity, and longterm photostability.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Compared with industrial hydrogen production and electrochemical hydrogen production, photocatalytic hydrogen evolution is undoubtedly the most sustainable and involves least energy consumption. 7 At present, among various semiconductors (such as CdS, [8][9][10] g-C 3 N 4 , [11][12][13] and TiO 2 (ref. 14 and 15)) as photocatalysts, titanium dioxide (TiO 2 ) is considered to be the most suitable photocatalyst for hydrogen production via water splitting due to its low cost, nontoxicity, high catalytic selectivity, and longterm photostability.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest charge transfer resistance of CoP/RP/BCN facilitates charge carrier separation and migration. 85,86…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, Shi 'group [13] conducted an investigation on the thermal gas shocking synthesis and photocatalytic performance of 2D ultrathin oxygen doped g-C3N4 photocatalysts, and found that the electronic structure of oxygen-doped g-C3N4 photocatalysts was optimized and the carrier separation rate was significantly elevated. Jia and his coworkers [14] prepared S and O co-doped g-C3N4 nanosheets through a two-step annealing process with melamine as the g-C3N4 precursor for efficient hydrogen generation. Tang' group [15] developed a defect-engineering approach to prepared O dopant and N defect in g-C3N4 framework.…”
Section: Introductionmentioning
confidence: 99%